Role of MHC class I pathways in Mycobacterium tuberculosis antigen presentation - Witt, Karolina D. (Frontiers in Cellular and Infection Microbiology, 2023)
MHC class I antigen processing is an area of the immunology and cell biology cross-over, underappreciated in the context of non-viral host-pathogen interactions and development of vaccines where pathogen natural life cycle involves little presence in cytoplasm. The response to MHC-I receptors’ antigen presentation is cell death but also stimulation of memory cells ready for the next antigen re-occurrence. This review looks at MHC-I antigen processing pathway and potential alternative sources of the antigens, focusing on Mycobacterium tuberculosis (Mtb) as an intracellular pathogen that co-evolved with humans and developed an array of decoy strategies to survive in hostile environment by manipulating host immunity to own advantage. As that happens via selective antigen presentation process, reinforcement of the effective antigen recognition on MHC-I receptors may stimulate subsets of effector cells that act earlier and more locally. Vaccines against tuberculosis [TB] could potentially eliminate this disease, yet their development has been slow, and success limited in the context of this global disease spread. This review conclusions set out potential directions for MHC-I focused approaches in the next generation of vaccines.